Unemployment-Inflation Relationship in Germany - Abdullah Miraç Bükey; Murat Kalkan (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
The Federal Republic of Germany has been one of the historically remarkable countries socially and economically. In this context, one of the outstanding issues is undoubtedly the correlation between unemployment and inflation, which is at the intersection of economy and social policy. Therefore, in the study, the unemployment-inflation trade-off in Germany was examined with the help of macroeconomic data in the context of the Modified/Original Phillips Curve, which explores the unemployment-inflation relationship. The empirical study method is time series analysis, and the monthly data set covers the period from January 1992 to April 2023. According to the study's findings, no causality relationship could be detected between unemployment and inflation variables in Germany in the period, neither in the long run nor in the short run. Therefore, it shows that the German economy does not have to put up with the inflation problem in the fight against unemployment and the unemployment problem in the battle against inflation. In this respect, it would be beneficial to thoroughly examine the German labour market structure and monetary policy strategy in the literature.